Biological Nitrate Removal from Groundwater by Filamentous Media at Pilot Scale, 2015 - Leila Keshtgar; Ali Akbar Azimi (Shiraz University of Medical Sciences, 2016)
Background: The compounds which contain nitrogen entering the environment can cause some problems, such as eutrophication for water resources and potential risk for human health because of methemoglobinemia and cancer. Biological techniques are effective in removing nitrate. The aim of this study was to remove nitrate from groundwater using denitrification. The main objectives of this research were determining the reduction of water nitrate based on different retention time and also the effect of using grape extract as organic matter and electron acceptor in biological nitrate removal from water. Methods: In this experimental study, the effect of heterotrophic Pseudomonas separated from Shiraz wastewater treatment plant on removing nitrate from groundwater was investigated at pilot scale using grape extract as carbon source and filamentous media at constant pH (7±0.1) and temperature (20±1 °C). During this study, 2 pilots were made. Pilot number 1 was used for separation and growth of the above mentioned bacteria (Pseudomonas) that are able to remove nitrate. Pilot number 2 was also used for surveying the removal of nitrate by these bacteria. At least, 13 samples were examined in every retention time and each test was repeated for 2 or 3 times. Statistical analysis was performed in SPSS (ver.19) software using one-way repeated measures ANOVA, and Bonferroni tests. Results: According to the results, nitrate removal rates were 49%, 55%, 67% and, 67% at retention times of 1, 1.5, 2, and 2.5 hours, respectively. The best retention time was 2 hours with 67% removal rate (P<0.05). Conclusion: The results showed that using grape extract as the carbon source and proper growth of bacteria in filamentous media led to a significant increase in the removal rate